Is Bangladeshi RMG Sector Fit in the Global Apparel Business? Analyses the Supply Chain Management - Nuruzzaman, Nuruzzaman; Haque, Ahasanul; Azad, Rafiq (UI Scholars Hub, 2010)
In recent years, supply chain management (SCM) has been developed as essential management philosopy and practice for all business operations. As with other business management principles, SCM also applies to the textile and apparel industries. All the parties or members should cooperate with its downstream customers and upstream suppliers to achieve supply chain goal. This paper was designed as an exploratory study to investigate SCM practice and to create competitive advantages in textille and garments (apparel) industries through efficient supply chain management from the perspective of business process. Current conditions of SCM practice in textille and garments industries in Bangladesh were revealed after questionnaire survey. In this study an attempt has been taken to develop a more effective supply chain for Bangladeshi RMG to enjoy competitive advantage in the global apparel business through analyzing the current supply chain and investigating the relationship among the players in the supply chain. In the conclusion recommendation has been made to exclude a party from the current SCM.